A novel homozygous KY variant causing a complex neurological disorder. - Arif, Beenish; Rasheed, Arisha; Kumar, Kishore R; Fatima, Amara; Abbas, Ghazanfar; Wohler, Elizabeth; Sobriera, Nara; Lohmann, Katja; Naz, Sadaf (Eur J Med Genet, 2020)
Mutations in the gene kyphoscoliosis peptidase (KY) are known to cause myofibrillar myopathy-7 and hereditary spastic paraplegia. We investigated the genetic cause of a complex neurological phenotype in a consanguineous Pakistani family with four affected members, manifesting lower limb spasticity and weakness, toe walking, pes equinovarus, and a speech disorder. Genome-wide linkage analysis with microsatellite markers delineated chromosome 3q22.2-q24 harboring the disease gene. Whole exome sequencing was performed for two subjects, identifying a homozygous 14-bp frameshift deletion NM_178554.6:c.842_855del; p(Val281GlyfsTer18) in KY. The variant segregated with the phenotype and was absent from public databases and 100 ethnically matched controls. We confirm a novel homozygous KY variant causing a complex neurological phenotype in this family. A review of previously reported KY variants suggests that variants in this gene can cause a spectrum of neurological phenotypes.
Keywords: Child; Female; Frameshift Mutation; Gait; Homozygote; Humans; Male; Myopathies, Structural, Congenital; Pedigree; Peptide Hydrolases; Phenotype; Spastic Paraplegia, Hereditary; Speech